WOMEN 2019’s POLITICAL REPRESENTATION IN INDIA - Nargis, Anjuma Ahmed (ShodhKosh: Journal of Visual and Performing Arts, 2023)
In the same respect, while women are not very active participants in state and national election processes in India, they have registered a tremendous and progressive vote bank. This realisation of women that, although they are confined to the private sphere and continue to be politically irrelevant in their candidacy, are becoming politically active in voting booths is a significant issue in Indian democracy. The 2019 elections demonstrated the impressive ability of women voters who, for several years, have become the numerators of those who voted in many regions of the country. This has led to the numerous approach adjustments of political parties, particularly the BJP and the INC, in their electioneering activities to embrace women’s issues and to lean. Measures such as setting aside seats for women in the local government have over time fostered the pipeline to the current increases in women’s political involvement at the higher states. However, the interesting fact is the difference between the number of women who voted and those who are headed into the Parliament. Thus, studying its contribution toward focusing on the relations of increasing female participation in elections, changes in rationales and prospects, as well as the general context of Indian democracy, is crucial.